An oral health intervention for people with serious mental illness (Three Shires Early Intervention Dental Trial): study protocol for a randomised controlled trial - Jones, Hannah F.; Adams, Clive E.; Clifton, Andrew; Simpson, Jayne; Tosh, Graeme; Liddle, Peter F.; Callaghan, Patrick; Yang, Min; Guo, Boliang; Furtado, Vivek (BioMed Central, 2013)
Background Oral health is an important part of general physical health and is essential for self-esteem, self-confidence and overall quality of life. There is a well-established link between mental illness and poor oral health. Oral health problems are not generally well recognized by mental health professionals and many patients experience barriers to treatment.